Neighborhood walkability, deprivation and incidence of type 2 diabetes: A population-based study on 512, 061 Swedish adults. (January 2015) - Sundquist, Kristina; Eriksson, Ulf; Mezuk, Briana; Ohlsson, Henrik
Abstract: Neighborhood walkability has been associated with increased physical activity, but only a few studies have explored the association between walkability and health outcomes related to physical activity, such as type 2 diabetes. The aim of this study was to investigate the association between objectively assessed neighborhood walkability and the 4-year incidence of type 2 diabetes in a sample of 512, 061 Swedish adults aged 18 years and older. Neighborhoods were defined by 408 administratively defined geographical areas in the city of Stockholm. We found a negative association between walkability and type 2 diabetes (OR=1.33, 95% CI=1.13–1.55) that remained significant after adjusting for neighborhood deprivation. This association, however, no longer remained statistically significant after adjusting for individual socio-demographic factors. These results were also confirmed using a co-sibling design. Future studies are encouraged to further explore the potential effect of a broader array of the neighborhood built environment on health outcomes related to physical activity. Highlights: Objective assessments of walkability and incidence of type 2 diabetes. A total of 512, 061 adults were included in the analyses. The association between walkability and type 2 diabetes was negative in the crude models. Adjustment for individual socio-demographic factors diminished this association. Sibling analyses confirmed the results.